Pengaruh Manajemen Disiplin Kelas terhadap Motivasi dan Keterlibatan Siswa dalam Pembelajaran (International Forum of Researchers and Lecturers, 2025)
Classroom discipline management plays an important role in creating a conducive learning environment and influences students' motivation and engagement in learning. This study aims to analyze the effect of classroom discipline management on students' motivation and engagement in the teaching and learning process. The research method used is a quantitative approach with a survey technique involving students from various levels of education as respondents. Data were collected through questionnaires and analyzed using descriptive statistical techniques and linear regression. The results of the study indicate that effective classroom discipline management, which includes clear rules, consistency in application, and an approach that supports student development, significantly increases students' motivation to learn and engagement in learning. Thus, teachers are expected to be able to apply appropriate classroom discipline strategies to improve the quality of learning and students' academic outcomes.